2016
DOI: 10.5455/msm.2016.28.21-25
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Outpatient Service Quality on Patient Satisfaction in Teaching Hospitals in Iran

Abstract: Aim:The quality of services plays a primary role in achieving patient satisfaction. The main purpose of this study was to explore the effect of outpatient service quality on patient satisfaction in teaching hospitals in Iran.Methods:this cross-sectional study was conducted in 2014. The study sample included 500 patients were selected with systematic random method from the outpatient departments (clinics) of four teaching hospitals in Tehran. The survey instrument was a questionnaire consisted of 44 items, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
(54 reference statements)
5
24
0
2
Order By: Relevance
“…A study by Andaleeb (2001) found that service quality has significant impacts on patient satisfaction in the hospitals in a developing country. Similarly, according to Pouragha and Zarei (2016), service quality dimensions have significant impacts on outpatient satisfaction. Similarly, another study by Alghamdi (2014) found statistically significant impacts of service quality factors on patient satisfaction.…”
Section: Discussion Of the Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Andaleeb (2001) found that service quality has significant impacts on patient satisfaction in the hospitals in a developing country. Similarly, according to Pouragha and Zarei (2016), service quality dimensions have significant impacts on outpatient satisfaction. Similarly, another study by Alghamdi (2014) found statistically significant impacts of service quality factors on patient satisfaction.…”
Section: Discussion Of the Main Findingsmentioning
confidence: 99%
“…As the service quality and satisfaction are the antecedents of behavioural intentions of customers that customer satisfaction does not by itself creates lifetime value for customer (Appiah-Adu, 1999). According to Pouragha and Zarei (2016), service quality dimensions have significant impacts on outpatient satisfaction. Similarly, another study by Alghamdi (2014) found statistically significant impacts of service quality factors on patient satisfaction.…”
Section: Relationship Between Service Quality and Patient/customer Samentioning
confidence: 99%
“…Tangibles include medical equipment, physical care facilities and hospital physical environment and surroundings (Nguyen and Nguyen, 2014). Previously, a number of studies have found that tangibility is a significant dimension for patients to increase the level of their satisfaction (Odgerel, 2012;Alshatnawi and Amlus, 2016;Pouragha and Zarei, 2016). Hospitals with good infrastructure, equipment and neat personnel attract many patients.…”
Section: Tangibility and Outpatient Satisfactionmentioning
confidence: 99%
“…Experience with a health care service can have a direct influence on the patient's expectations of the services (Parasuraman et al, 1991;Amole et al, 2015). Outpatients' satisfaction is selected because according to Pouragha and Zarei (2016) patients' general impression towards a hospital relies significantly on the quality of the outpatient services and the most important part of a health care system is the hospital's outpatient department. To a patient, service quality is about satisfying the needs and providing the necessary medical services (Sathiyaseelan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tangibles include medical equipment, physical care facilities and hospital physical environment and surroundings (Nguyen and Nguyen, 2014). Previously, a number of studies have found that tangibility is a significant dimension for patients to increase the level of their satisfaction (Odgerel, 2012;Alshatnawi and Amlus, 2016;Pouragha and Zarei, 2016). Hospitals with good infrastructure, equipment and neat personnel attract many patients.…”
Section: Tangibility and Outpatient Satisfactionmentioning
confidence: 99%